DAYA TAMPUNG SUNGAI REMBAGAN TERHADAP BEBAN PENCEMARAN MENGGUNAKAN METODE STREETER-PHELPS - Sri Wahyuningsih; Elida Novita; Irfan Dwi Satya (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Rembagan River is the main tributary of the Bedadung River in Cangkring Village, Patrang District, Jember Region. Various community activities in the Rembagan River area such as bathing, washing, defecating and urinating as well as agricultural activities will produce domestic and agricultural waste. These wast can cause river water pollution, especially water quality degradation. then the research needs to be done an analysis of the capacity of the Rembagan River in receiving pollution costs. The purpose of this study is to find out how much the ability of the Rembagan River to accept the burden of pollutants using the Streeter-Phelps method. Streeter-Phelps modeling takes into account two phenomena, namely the process of measuring dissolved oxygen (deoxygenation) and the process of increasing dissolved oxygen (reaeration). The results obtained from these calculations are oxygen drop curves determined on the basis of oxygen deficit values. The average values of deoxygenation rate and reoxygenation rate were sequentially 1.58931 mg/L/day and 10.09982 mg/L/day. So that self-purification can run well which means the water quality of the Rembagan River was still relatively good. This can be seen in the DO model pattern that goes up in each segment. The actual DO of 5.6760 mg / L was greater than the DO standard of class III quality of 3 mg / L. It can be interpreted that the Rembagan River still has a remaining DO of 2.676 mg / L and was still able to accept pollution cost of 18.8 kg/day. Keywords:  pollution load, Rembagan River, river capacity